Genetic architecture underlying IgG-RF production is distinct from that of IgM-RF. (17th October 2022) - Yaku, Ai; Ishikawa, Yuki; Iwasaki, Takeshi; Hiwa, Ryosuke; Matsuo, Keitaro; Saji, Hiroh; Yurugi, Kimiko; Miura, Yasuo; Furu, Moritoshi; Ito, Hiromu; Fujii, Takao; Maekawa, Taira; et al.
Abstract: Objective: HLA-DRB1 alleles, particularly the shared epitope (SE) alleles, are strongly associated with RA. Different genetic structures underlie the production of the various autoantibodies in RA. While extensive genetic analyses have been conducted to generate a detailed profile of ACPA, a representative autoantibody in RA, the genetic architecture underlying subfractions of RF other than IgM-RF, namely IgG-RF, known to be associated with rheumatoid vasculitis, is not well understood. Methods: We enrolled a total of 743 RA subjects whose detailed autoantibody (IgG-RF, IgM-RF, and ACPA) data were available. We evaluated co-presence and correlations of the levels of these autoantibodies. We analysed associations between the presence or levels of the autoantibodies and HLA-DRB1 alleles for the 743 RA patients and 2008 healthy controls. Results: We found both IgG-RF(+) and IgG-RF(–) RA subjects showed comparable associations with SE alleles, which was not observed for the other autoantibodies. Furthermore, there was a clear difference in SE allele associations between IgG-RF(+) and (–) subsets: the association with the IgG-RF(+) subsets was solely driven by HLA-DRB1*04:05, the most frequent SE allele in the Japanese population, while not only HLA-DRB1*04:05 but also HLA-DRB1*04:01, less frequent in the Japanese population but the most frequent SE allele in Europeans, were main drivers of the association in the IgG-RF(–) subset. We confirmed that these associations were irrespective of ACPA presence. Conclusion: We found a unique genetic architecture for IgG-RF(–) RA, which showed a strong association with a SE allele not frequent in the Japanese population but the most frequent SE allele in Europeans. The findings could shed light on uncovered RA pathology. Graphical Abstract: